Predicting Tobacco Use Based on the Theory of Planned Behavior in Adolescent Girls - Maryam Ghasemipour; Rabiollah Farmanbar; Parisa Kasmaee; Zahra Atrkar Roshan; Sima Nickandish (Guilan University of Medical Sciences, 2021)
Introduction: Tobacco use poses a serious threat to global health. The tobacco epidemic is spreading in low- and middle-income countries, where the tobacco industries mainly target young people and women. Objective: This study aims to determine the predictors of tobacco use based on the theory of planned behavior (TPB) in female high school students. Materials and Methods: This cross-sectional study was conducted on 340 female high school students aged 14-18 years in Rasht City, Iran, who were selected using a multi-stage sampling method. The data collection tool was the TPB questionnaire for tobacco use in Persian. The obtained data were analyzed using the Mann-Whitney U test, Kolmogorov-Smirnov test, Spearman correlation test and logistic regression analysis. Results: The TPB constructs of attitude (OR = 0.91, 95% CI: 0.85-0.97, P = 0.007) and behavioral intention (OR=0.75, 95% CI; 0.64-0.88, P = 0.001) could predict cigarette smoking. Also, constructs of perceived behavioral control (OR = 0.92, 95%CI; 0.87-0.97, P = 0.007), subjective norms (OR = 0.83, 95%CI; 0.70-0.97, P = 0.02), and behavioral intention (OR = 0.88, 95% CI; 0.78 - 0.99, P = 0.03) could predict hookah smoking in girls students. Conclusion: Considering the predictive power of the TPB constructs in tobacco use by adolescent girls, it is possible to plan to reduce its rate in this group by a focus on the TPB constructs.